Performance of geopolymer concrete subjected to mineral acid corrosion and related to microbially-induced corrosion (MIC) of concrete in sewers - Dlamini, Mandla (Department of Civil Engineering, 2021)
worse than degradation at the crown of the sewer pipe. Furthermore, results from this study show that high resistance under the static acid corrosion exposure condition cannot be extended to mean high resistance under the erosion-corrosion exposure condition for some concrete mixes. In this study, the static HCl test and the dynamic HCl test were used to measure the resistance of concrete mixes under the static corrosion exposure condition and erosion-corrosion exposure condition respectively. However, concretes that exhibited high resistance to the erosion-corrosion exposure condition were consistent in exhibiting high resistance to the static corrosion exposure condition. This finding is consistent with the sequence of corrosion processes in MIC, wherein dissolution of the concrete components occurs before the precipitation of corrosion products. Therefore, it expected that high resistance in the dynamic acid test (i.e. resistance to dissolution) implies high resistance in the static test, which measures the combined resistance of dissolution and resistance emanating from corrosion products. Both static and dynamic acid corrosion tests revealed that the geopolymer concretes tested in this study outperformed PC and CAC concretes. Results from the static HCl test showed that GP-ferro-quartz concrete, the most durable concrete specimen, provided a 69-fold improvement in resistance when compared to PC-dolomite mixes (control #1) and a 4.72-fold improvement in resistance when compared to CAC-dolomite mixes (control #2). Results from the dynamic HCl test show that the GP-ferro-quartz mix provided a 180-fold increase in resistance when compared to the PC-dolomite mix and a 275-fold increase when compared to CAC-dolomite mix. The CACdolomite mix was found to have the lowest resistance to the erosive-corrosive exposure conditions of the dynamic HCl test. Thus, in terms of the concrete MIC resistance properties identified in this study, it is suggested that the CAC-dolomite mix had poor kinetic resistance to dissolution. However, under the static acid test (static corrosion exposure condition), the CAC-dolomite mix performed better than the PC-dolomite mix and GP-dolomite mix. CAC-dolomite concrete performed inferiorly only to the set of GP-siliceous-aggregate mixes in the static HCl test. The difference in the performance of CAC-dolomite concrete performance between the static and dynamic test is largely attributed to the formation of alumina gel, an acid corrosion product of CAC hardened paste, which envelopes the concrete specimen and reduces the rate of surface corrosion in the static HCl test. However, under v the dynamic HCl test, the gel layer is brushed off the surface of the concrete specimen rendering it ineffective in protecting the concrete specimen from corrosion. Previous research on the acid attack of concrete posits that the chemical make-up of concrete materials has a strong bearing on corrosion behaviour. To this end, various measures have been suggested such as the ratio of calcium to silicon (Ca/Si) in concrete. The approach utilised in this study was to calculate the “basicity value” which provides the ratio of major basic to acidic oxides found in the concrete. XRF analysis of the hardened cement pastes and the 5 aggregate types used in the experiments enabled the calculation of basicity values. The combined basicity value for concrete specimens was determined by proportionally summing (according to mass) the basicity values of the aggregate and hardened cement paste parts. A strongly correlated linear relationship between the basicity value of concrete and the corrosion rate from the dynamic HCl test was established. This empirical relationship warrants further investigation and verification, as it would, in principle provide a means to estimate the dissolution rate of concrete by calculating its basicity instead of undertaking laboratory acid tests. Basicity was also found to be useful in determining the corrosion compatibility of binder type and aggregate types. It was found that the difference between the basicity value of hardened cement paste and the basicity value of the aggregate was useful in determining the type and extent of preferential corrosion of a concrete specimen tested under the dynamic HCl test. For ease of reading, this difference was called the “basicity differential”. By visually assessing corroded concrete specimens from the dynamic HCl test, it is was possible to determine whether the hardened cement paste or aggregate component was preferentially corroded, and to gauge the extent of preferential corrosion visually. GP-ferro-quartz and GP-granite concretes had the lowest levels of preferential corrosion which corresponded to their low basicity differential values. In contrast, CAC-dolomite concrete had the highest basicity discrepancy which corresponded visually to a high preferential corrosion of the hardened cement paste. Mineralogical analysis via XRD, found that the hardened cement pastes of the three binder types consisted mainly of amorphous phases (>70%). The crystalline phase of the geopolymer hardened cement paste was mostly constituted by insoluble minerals such as mullite. This partially explains the higher corrosion resistance of geopolymer concretes. However, a more comprehensive explanation needs to include analysis of the amorphous phases, which fell outside the scope of this study. SEM analysis of HCl corroded geopolymer hardened cement paste found that fly ash spheres embedded within the geopolymer matrix were preferentially corroded. This indicates that fly ash content negatively affected the rate of corrosion of the geopolymer hardened cement paste. Furthermore, SEM analysis showed that the geopolymer matrix surrounding the fly ash spheres was relatively intact.